Response of Surface Erosion to Crustal Shortening and its Influence on Tectonic Evolution in Fold‐and‐Thrust Belts: Implications From Sandbox Modeling on Tectonic Geomorphology. Issue 5 (25th May 2021) - Mao, Yuqiong; Li, Yiquan; Yan, Bing; Wang, Xianyan; Jia, Dong; Chen, Yingying
Abstract: Structural deformation affects surface processes and the consequent distribution of tectonic stress and structural deformation patterns via crustal isostasy. The associated processes and mechanisms are widely concerned topics in tectonic geomorphology. In this study, we discuss the interaction between tectonic deformation and surface processes in fold‐and‐thrust belts by sandbox experimental modeling. The tectonic deformation patterns under different conditions are studied, including the occurrence of detachment and the different crustal shortening rates. Furthermore, we discussed the influence of surface erosion and sedimentation on the spatial distribution, morphology, amplitude, and process of tectonic deformation. The results show that the occurrence of plastic detachment links the interaction of surface erosion and tectonics such as deformation patterns. Thin‐skinned structures develop when plastic detachment occurs, thus amplifying surface processes. In turn, the erosion and deposition affect the position and morphology of new structures as well as the lateral propagation and connection of isolated structures. Different shortening rates lead to different propagation distances and structure arrangements. These different tectonic conditions result in diverse drainage evolution and the specific processes of surface erosion and deposition. In general, structural development is controlled by both endogenic forces and surface erosion and deposition processes. The physical properties of detachments and crustal shortening rates play an important role in linking deep tectonic activity and surface processes. These results are comparable to natural examples, such as the fold‐and‐thrust belts along the Tianshan Mountains, thus providing new clues for understanding the mechanism of the interaction between endogenic tectonic activity and surface processes. Key Points: Crustal shortening rates influence structural array arrangements and drainage system evolution Surface erosion and sedimentation affect the position, morphology, lateral propagation, and connection of new structures Plastic detachments link deep tectonic activity and surface erosion by forming thin‐skinned structures that amplify surface processes